Factors influencing the latency of simple reaction time - Woods, David L.; Wyma, John M.; Yund, E. William; Herron, Timothy J.; Reed, Bruce (Frontiers in Human Neuroscience, 2015)
Simple reaction time (SRT), the minimal time needed to respond to a stimulus, is a basic measure of processing speed. SRTs were first measured by Francis Galton in the 19th century who reported visual SRT latencies below 190 ms in young subjects. However, recent large-scale studies have reported substantially increased SRT latencies that differ markedly in different laboratories, in part due to timing delays introduced by computer hardware and software used for SRT measurement. We developed a calibrated and temporally-precise SRT paradigm to analyze the factors that influence SRT latencies in a paradigm where visual stimuli were presented to the left or right hemifield at varying stimulus onset asynchronies (SOAs). Experiment 1 examined a community sample of 1469 subjects ranging in age from 18 to 65. Mean SRT latencies were short (231 ms, 213 ms when corrected for hardware delays) and increased significantly with age (0.55 ms/year), but were unaffected by sex or education. As in previous studies, SRTs were prolonged at shorter SOAs and were slightly faster for stimuli presented in the visual field contralateral to the responding hand. Stimulus detection time (SDT) was estimated by subtracting movement-initiation time, measured in a speeded finger-tapping test, from SRTs. SDT latencies averaged 131 ms and were unaffected by age. Experiment 2 tested 189 subjects ranging in age from 18 to 82 years in a different laboratory using a larger range of SOAs. Both SRTs and SDTs were slightly prolonged (by 7 ms). SRT latencies increased with age while SDT latencies did not. Precise computer-based measurements of SRT latencies show that processing speed is as fast in contemporary populations as in those from the Victorian era and that age-related increases in SRT latencies are due primarily to slowed motor output.